Study on the Extraction of Urban Water Systen and River Basin Based on Multiple-source DEM Fusion - LIU Jiajia; ZHOU Zuhao; LIU Lin; LU Bin; DAI Dongchen; ZHU Jiasong; YAN Ziqi (Renmin Zhujiang)
There is difference on extraction of urban water system and river basin because different data source of DEM has a different elevation error. In order to reduce the impact of single DEM error, this paper proposes an effective way to improve the DEM accuracy by fusing the multi-source DEM and reducing the local error. The results demonstrate that the fusing DEM shows a greater accuracy in extracting the water system and river basin. Moreover, the application of Pingshan River reveals that it could get the best result by averaging the elevation of two different Source DEM with comprehensive consideration of accuracy errors of water system and river basin.